Boosting ultrathin aSi-H solar cells absorption through a nanoparticle cross-packed metasurface. (15th May 2020) - Elshorbagy, Mahmoud H.; López-Fraguas, Eduardo; Sánchez-Pena, José Manuel; García-Cámara, Braulio; Vergaz, Ricardo
Graphical abstract: Highlights: A nanostructure ITO with engraved crosses filled with 5 dielectric nanospheres. This metasurface enhances optical absorption in an a-Si hydrogenated solar cell. Mie resonant nanoparticles and crosses guide and confine light in active layer. It reduces active layer thickness and degradation, improving charge extraction. A simulation procedure achieves the best radius and refractive index of particles. Abstract: Hydrogenated amorphous silicon (a-Si:H) solar cells have some performance limitations related to the mobility and lifetime of their carriers. For this reason, it is interesting to explore thin-film solutions, achieving a tradeoff between photons optical absorption and the electrical path of the carriers to get the optimum thickness. In this work, we propose the insertion of a metasurface based on a cross-patterned ITO contact film, where the crosses are filled with nanospheres. We numerically demonstrate that this configuration improves the photogenerated current up to a 40% by means of the resonant effects produced by the metasurface, being independent on the impinging light polarization. Light handling mechanisms guide light into the active and auxiliary layers, increasing the effective absorption and mitigating the Staebler-Wronski effect. The selection of optimum materials and parameters results in nanospheres of ZnO with a 220 nm radius.